Marginal zone lymphoma in a dog. (10th June 2020) - Burgess, Hilary J.; MacDonald Dickinson, Valerie; Kerr, Moira; Bienzle, Dorothee
Abstract: A 13‐year‐old spayed female American Cocker Spaniel was presented for evaluation of a cough and weight loss. Physical exam revealed generalized lymphadenopathy. The patient was diagnosed with marginal zone lymphoma (MZL) on histopathology of an extirpated lymph node. This report demonstrates an unusual case of a pleomorphic neoplastic population documented on cytologic evaluation that had moncytoid features and peripheral blood involvement; a previously undocumented IgG1 monoclonal gammopathy was also an interesting feature of this canine MZL. The patient did not undergo chemotherapy for lymphoma and was euthanized over 4 years after the initial presentation.